2018
DOI: 10.1080/13102818.2018.1460622
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the antitumour efficacy of the biocompound IMMUNEPOTENT CRP by enzymatic treatment

Abstract: IMMUNEPOTENT CRP is a dialyzable leukocyte extract obtained from bovine spleen with immunomodulatory and antitumour properties; therefore, when administrated as an adjuvant therapy for cancer patients, it has increased their survival and quality of life. The bioavailability of any orally administered compound can be reduced due to gastrointestinal enzymes. In this study, we evaluated if IMMUNEPOTENT CRP is resistant to the treatment with different enzymes (proteases, nucleases, polysaccharide-degrading enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We induced the air pouch model, inoculated L5178Y-R cancer cells, and determined if our compound interfered with tumor implantation. We concluded that our bio-compound has antitumor properties [59].…”
mentioning
confidence: 79%
“…We induced the air pouch model, inoculated L5178Y-R cancer cells, and determined if our compound interfered with tumor implantation. We concluded that our bio-compound has antitumor properties [59].…”
mentioning
confidence: 79%
“…Similar treatments for leukemia have been difficult to find because this being a cancer of the immune system and it is unclear whether the drugs will distinguish between healthy and cancerous cells [10]. I-CRP shows selective cytotoxicity to solid cancer cells [16,20,21,23], such as MCF-7, BT-474, MDA-MB-453, A-427, Calu-1, U937, and L5178Y-R cell lines [20,21,23]. Other types of DLE have also shown antitumor activity in prostate cancer [29] and can be used in combination with chemotherapies [30] and with antibiotics as manumycin in mouse breast cancer (4T1) [31].…”
Section: Discussionmentioning
confidence: 99%
“…IMMUNEPO-TENT-CRP© (I-CRP) is an immunotherapeutic agent composed of bovine dialyzable leukocyte extract (bDLE) obtained from disintegrated spleen. In previous reports, I-CRP showed a potential immunomodulatory effect in preclinical trials of breast cancer treatments, [14,15] and in in vivo assays, it showed an antitumor effect [16,17]. Several in vitro studies reveal its immunomodulatory properties in human and mouse monocytes and macrophages [18,19] and their cytotoxic effect in different cancer cell lines [20,21].…”
Section: Introductionmentioning
confidence: 93%
“…Besides its chemo-protective activity, IMMUNEPOTENT CRP has cytotoxic effect against several cancer cell lines, including MCF-7, BT-474, MDA-MB-453 (breast cancer) , A-427, Calu-1 (lung cancer) , U937 (leukemia) , and L5178Y (lymphoma) [13], B16F10 (melanoma) [14], K562, MOLT-3 (human leukemia) [15], and HeLa (cervical cancer) [16] in vitro; also, toxic doses for cancer cells do not affect human PBMC [13] human monocytes, and murine peritoneal macrophage [15]. Furthermore, IMMUNEPOTENT CRP possesses antitumor activity against murine lymphoma [16] and melanoma [17] in a dose-dependent manner. The search for novel drugs is still a priority goal for cancer therapy due to the inefficiency, high toxicity, adverse effects and development of resistance to chemotherapeutic drugs.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Higher doses caused too much discomfort and severe pain. It is reasonable to assume that this is the reason why complete tumor regression was not achieved in the murine models [16,17]. On the contrary, with 50 units administrated to dogs by the intravenous route, there are no signs of discomfort or pain [data not published yet].…”
Section: Biological Propertiesmentioning
confidence: 99%